Penerapan SAK EMKM dalam Penyusunan Laporan Keuangan UMKM di Sketsa Caffe Kota Pekanbaru - Berry, Berryan Intanio (CV. Kalimasada Group, 2023)
MSMEs are one of the various types of micro-enterprises that have excellent potential to support the economy in Indonesia, especially in one of the businesses in Pekanbaru, namely MSMEs at SKETSA Cafe, so this research has the aim of examining the obstacles encountered by actors from MSMEs in the preparation of financial reports in accordance with SAK EMKM in order to design a simple financial reporting system based on SAK EMKM. This research was conducted with a qualitative approach and used a case study method. The data sources used are secondary data and primary data. The data collection method is carried out through observation, documentation and interviews. The results of the analysis of this study show that business actors have not implemented the preparation of financial reports such as the SAK EMKM standard. and the obstacles experienced by MSME business owners at the SKETSA cafe are the lack of socialization and information regarding the implementation of SAK EMKM, the low capital owned by business actors to use expert staff in compiling financial reports, and the absence of regulations related to the implementation of SAK EMKM so that this makes business actors only prepare a simple financial reporting system.